PHARMACOLOGIC ACTIVATION OF THE ALTERNATIVE RAS ATTENUATES DEVELOPMENT OF PULMONARY ARTERIAL HYPERTENSION IN MONOCROTALINE TREATED RATS. (April 2021) - Vigl, Benjamin; Trubacova, Simona; Poglitsch, Marko; Domenig, Oliver; Balis, Peter; Barta, Andrej; Valovic, Pavol; Liskova, Silvia; Simko, Fedor; Paulis, Ludovit
Abstract : Objective: Pulmonary arterial hypertension (PAH) is a rare, chronic and debilitating disease characterized by increased pulmonary arterial pressure leading to right heart failure and – eventually death. Several drugs are approved for the treatment of PAH, but due to ongoing disease progression only half of the patients survive more than 7 years after diagnosis. A novel therapeutic approach based on pharmacologic activation of the alternative RAS was investigated in monocrotaline induced PAH in rats. Design and method: PAH was induced in 12 week-old Wistar rats by an injection of monocrotaline (60 mg/kg). Immediately after PAH induction, the rats (n = 11-12 in each group) were treated for 4 weeks with either a) vehicle, b) the novel peptidase inhibitor ALT001, or c) the endothelin receptor antagonist bosentan – representing the standard of care. Vehicle-treated sham rats served as healthy controls. Analysis included tissue and plasma equilibrium levels of angiotensin metabolites, echocardiography determined right ventricular function and structure, pulmonary arterial pressure, systemic blood pressure and histomorphometrical evaluations. Results: Ang II was significantly increased in lungs of monocrotaline treated animals concomitant with a profound increase in pulmonary arterial pressure (mPAP), reduced fractional shortening, dilated pulmonary valve diameter and a thickened and enlarged right ventricle. ALT001 treatment resulted in increased Ang 1–7 levels while Ang II levels were normalized. Bosentan treatment did not affect angiotensin peptide levels. The PAH induced increase in mPAP was almost completely abolished by ALT001 treatment, while systemic blood pressure remained unaffected. Right ventricular structure and function was effectively preserved under ALT001 treatment and pathological changes in fractional shortening (FS) were significantly reduced. Conclusions: Small molecule based modulation of the RAS might represent a promising novel therapeutic approach in treating RAS-related diseases, including PAH. (Partly supported by VEGA 1/0127/17, FFG 872313)